2022
DOI: 10.1038/s41598-022-08485-6
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial influence of environmental temperature, obesity and cholesterol on SARS-CoV-2 infectivity

Abstract: The continuing evolution of SARS-CoV-2 variants not only causes a long-term global health concerns but also encounters the vaccine/drug effectiveness. The degree of virus infectivity and its clinical outcomes often depend on various biological parameters (e.g., age, genetic factors, diabetes, obesity and other ailments) of an individual along with multiple environmental factors (e.g., air temperature, humidity, seasons). Thus, despite the extensive search for and use of several vaccine/drug candidates, the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…These results are consistent with literature data on cholesterol effects on SARS-CoV-2 infectivity. [42] , [43] , [44] , [45] , [46] Our simulations also reveal preference of SDS to RBD and high affinity of all surfactants considered to the recently discovered fatty acid binding site. Analysis of interactions of different surfactant functional groups, represented by hydrophilic head, hydrophobic tail, cationic and anionic beads, with the S1 residues shows that anionic head groups are preferred by the protein compared to cationic ones.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…These results are consistent with literature data on cholesterol effects on SARS-CoV-2 infectivity. [42] , [43] , [44] , [45] , [46] Our simulations also reveal preference of SDS to RBD and high affinity of all surfactants considered to the recently discovered fatty acid binding site. Analysis of interactions of different surfactant functional groups, represented by hydrophilic head, hydrophobic tail, cationic and anionic beads, with the S1 residues shows that anionic head groups are preferred by the protein compared to cationic ones.…”
Section: Discussionsupporting
confidence: 55%
“…The strong interaction of cholesterol with S1 domain found in our simulations is consistent with the observations that have been made regarding the cholesterol effects on COVID-19 disease. [42] , [43] , [44] , [45] , [46] An early study [42] reported that CHOL-rich microdomains in the plasma membrane facilitates the Spike-ACE2 interaction. The influence of cholesterol on the SARS-CoV infectivity was found to be solely due to the Spike-CHOL interaction and not due to CHOL interaction with any other coronavirus protein.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that since the pandemic started, many authors have analyzed the issue of impact of many factors (weather conditions, air pollution and etc.) on COVID-19 incidence, severity, and mortality, and literature linking to this issue has increased exponentially and now hundreds studies show the different results (see related revies in (Kang et al, 2021; Prévost et al, 2021; Liang & Yuan, 2022; Mandal et al, 2022; McClymont & Hu, 2021; Mejdoubi et al, 2020; Runkle et al, 2020; To et al, 2021; Tripathi et al, 2022; Xie & Zhu, 2020; Carballo et al, 2022; Culqui et al, 2022; Ishmatov, 2022; Kang et al, 2021; Perone, 2022; Taylor et al, 2022)). Most of the studies are statistical and analyze the correlation between various influencing factors.…”
Section: Resultsmentioning
confidence: 99%
“…It is worth noting that today there are many studies of the correlation of weather factors and air temperature with COVID-19 in many countries and cities. Most of them agree that air temperature affects COVID-19 and authors describe some possible effects of air temperature on COVID-19 disease severity and transmission rates (see related reviews in (Kang et al, 2021; Prévost et al, 2021; Liang & Yuan, 2022; Mandal et al, 2022; McClymont & Hu, 2021; Mejdoubi et al, 2020; Runkle et al, 2020; Tripathi et al, 2022).…”
Section: Resultsmentioning
confidence: 99%